Interdependencies among the Irish, British and German stock markets - Gallagher, Liam (Economic & Social Studies, 1995)
Interdependencies between the Irish stock market and two other stock markets, namely the United Kingdom and Germany, are assessed. The indices used are the ISEQ, the FTSE-100, and the FAZ. The application of cointegration techniques suggest that a long-run relationship does not exist between either the stock markets' price levels or their rates of return. There is however, a significant increase in the correlation between short-run returns across the markets after the 1987 stock market crash. Greater stock market integration has coincided with greater financial and economic integration. No lead-lag relationships are found for the pre-crash period in applying Granger causality tests. However, important uni-directional causality is found for the post-crash period. Indicating that the Irish stock market is inefficient. Significant contemporaneous causality is detected for the period of the stock market crash.
Keywords: Economic interdependence; Stock markets; Ireland; United Kingdom; Germany